Review of East Asian Heliosia (Ledidoptera: Erebidae: Arctiinae: Lithosiini) species, with description of a new genus - Dubatolov, Vladimir V.; Kishida, Yasunori; Wu, Chunsheng (Zootaxa, 2014)
Oriental species currently classified in the genus Heliosia Hampson, 1900 but in fact belonging to Nudariini are separated into the new genus Paraheliosia gen. nov.: Paraheliosia elegans (Reich, 1937) comb. nov. (type species) from South-East China; P. rufa (Leech, 1890) comb. nov. from North China (nominotypical subspecies) and Primorskiy Kray of Russia (P. r. ussuriensis (O. Bang-Haas, 1927) comb. nov.); and P. novirufa (Fang, 1992) comb. nov. from Sichuan. Presence of two strong apical spines at juxta apex and basal costal valve processes looks to be well marked autapomorphic characters of the new genus. Heliosia punctata Fang, 1992 is transferred into Elachistidae, Aeolanthinae but to unknown genus.